Human health risks associated with antimicrobial-resistant enterococci and Staphylococcus aureus on poultry meat. (February 2016) - Bortolaia, V.; Espinosa-Gongora, C.; Guardabassi, L.
Abstract: Enterococci and staphylococci are frequent contaminants on poultry meat. Enterococcus faecalis, Enterococcus faecium and Staphylococcus aureus are also well-known aetiological agents of a wide variety of infections resulting in major healthcare costs. This review provides an overview of the human health risks associated with the occurrence of these opportunistic human pathogens on poultry meat with particular focus on the risk of food-borne transmission of antimicrobial resistance. In the absence of conclusive evidence of transmission, this risk was inferred using data from scientific articles and national reports on prevalence, bacterial load, antimicrobial resistance and clonal distribution of these three species on poultry meat. The risks associated with ingestion of antimicrobial-resistant enterococci of poultry origin comprise horizontal transfer of resistance genes and transmission of multidrug-resistant E. faecalis lineages such as sequence type ST16. Enterococcus faecium lineages occurring in poultry meat products are distantly related to those causing hospital-acquired infections but may act as donors of quinupristin/dalfopristin resistance and other resistance determinants of clinical interest to the human gut microbiota. Ingestion of poultry meat contaminated with S. aureus may lead to food poisoning. However, antimicrobial resistance in the toxin-producing strains does not have clinical implications because food poisoning is not managed by antimicrobial therapy. Recently methicillin-resistant S. aureus of livestock origin has been reported on poultry meat. In theory handling or ingestion of contaminated meat is a potential risk factor for colonization by methicillin-resistant S. aureus . However, this risk is presently regarded as negligible by public health authorities.